Venous thromboembolism risk for patients with BMI ≥40 kg/m2 undergoing robotic surgery for endometrial cancer - Kaitlyn G. Dinkins; Grace M. Lee; Peter W. Ketch; Michael D. Toboni; Charles A. Leath, III; J.Michael Straughn, Jr.; Teresa K.L. Boitano (Gynecologic Oncology Reports)
Objectives: To determine the 30-day postoperative incidence of venous thromboembolism (VTE) in patients with endometrial cancer and body mass index (BMI) ≥40 kg/m2 undergoing robotic surgical staging. Methods: This retrospective cohort study included patients undergoing robotic surgery for endometrial cancer from January 2020 to December 2022 with BMI ≥40 kg/m2 at a single academic institution. Patients were excluded if they were prescribed therapeutic anticoagulation preoperatively. Age, race, BMI, ECOG performance status, Charlson Comorbidity Index (CCI), estimated blood loss, and operative time were collected. Postoperative outcomes including postoperative VTE rate within 30 days of surgery, 30-day readmission, and 30-day mortality were assessed. The primary outcome was the 30-day postoperative rate of VTE. SPSS v28 was used for statistical analysis. Results: Of the 127 patients included, average BMI was 47 kg/m2 with 26.8 % of patients having a BMI ≥50 kg/m2. Most patients were white (63.2 %), had a CCI of 3–5 (75.6 %), and Stage I disease (84.3 %). The rate of VTE within 30 days of surgery was 0 %. 30-day readmission rate was 3.9 % and 30-day mortality rate was 1.6 %. All patients received mechanical prophylaxis intraoperatively and 67.7 % of patients received preoperative subcutaneous heparin. Of the patients admitted postoperatively (78.8 %), all received mechanical prophylaxis and 79.0 % received chemoprophylaxis with low molecular weight heparin while inpatient. Conclusion: The rate of 30-day postoperative VTE following robotic staging in patients with class III obesity and endometrial cancer is low. Given this result, these patients do not routinely require extended anticoagulation prophylaxis for VTE prevention upon discharge.